2019
DOI: 10.3390/biom9100625
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Polyarginine Peptide with Membranes of Different Mechanical Properties

Abstract: The membrane translocation efficiency of cell penetrating peptides (CPPs) has been largely studied, and poly-arginines have been highlighted as particularly active CPPs, especially upon negatively charged membranes. Here we inquire about the influence of membrane mechanical properties in poly-arginine adsorption, penetration and translocation, as well as the subsequent effect on the host membrane. For this, we selected anionic membranes exhibiting different rigidity and fluidity, and exposed them to the nona-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 63 publications
4
35
0
Order By: Relevance
“…The membrane deformations are thought to be caused by the charge neutralization, which can lead to a decrease in bending rigidity. A similar behavior was described for the TAT peptide by Herce et al, discussed in more detail in a previous section (Direct translocation mechanisms used by arginine-rich peptides), where the incorporation of water into the membrane together with the peptide as well as membrane thinning have been mentioned [47,48,123].…”
Section: Role Of Membrane Propertiessupporting
confidence: 64%
See 1 more Smart Citation
“…The membrane deformations are thought to be caused by the charge neutralization, which can lead to a decrease in bending rigidity. A similar behavior was described for the TAT peptide by Herce et al, discussed in more detail in a previous section (Direct translocation mechanisms used by arginine-rich peptides), where the incorporation of water into the membrane together with the peptide as well as membrane thinning have been mentioned [47,48,123].…”
Section: Role Of Membrane Propertiessupporting
confidence: 64%
“…However, less is known about the influence of the plasma membrane properties on the uptake. The number of studies on this topic is rather narrow, however, information about the impact of plasma membrane composition and how it changes and adapts is available from studies using poly-arginines [123].…”
Section: Role Of Membrane Propertiesmentioning
confidence: 99%
“…A previous study using P. aeruginosa (a hopanoid-lacking bacteria) has shown that cells preincubated with CHO or DP, exhibit decreased permeability and sensitivity to cell wall biosynthesis inhibitors, carbenicillin, and imipenem (Mangiarotti et al, 2019a). This behavior correlates with the changes induced by the presence of CHO or DP in the properties of artificial lipidic membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The used optical trap equipment has been described previously (Crosio et al, 2019). Briefly, a 3W power ND:YVO4 laser (Spectra-Physics, Santa Clara, CA, USA) was focused through a 100x objective (water immersion, NA = 1, Zeiss).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation